Outcome of volar Barton fractures of distal radius managed with open reduction and internal fixation with volar locking plate - Lone, Sukhil Raina; Tanveer Ahmed Bhat; Zubair Ahmad Lone; Neeraj Mahajan; Farid Hussain Malik; Mohammed Farooq Butt; Sanjeev Gupta (International Journal of Research in Medical Sciences, 2023)
Background: Volar Barton fractures of distal radius almost always require a surgical fixation. Near anatomical reduction and a stout fixation is imperative for good outcome. The present study aimed at studying the outcome of open reduction and internal fixation with volar locking plate for volar Barton fractures. Methods: The present study included 25 patients with volar Barton fractures of distal radius presenting to the orthopaedic department who were managed with volar locking plate. The minimum follow-up period was 12 months. Wrist movements were recorded and outcome was studied using modified mayo wrist score at final follow-up. Results: The mean modified mayo wrist score at final follow-up was 88.47±15.3. Excellent to good outcome was observed in 80% of the patients. None of the patients had a poor outcome. Clinically significant movements were observed at wrist at final follow-up. Superficial wound infection was the most common complication and deep infection was seen in two patients and both of them needed early implant removal at three months. Hypertrophic scar at surgical incision site was observed in two patients but did not bother the patients. Two patients needed a stellate ganglion block and physiotherapy for complex regional pain syndrome (CRPS) and both responded well. Conclusions: Open reduction and internal fixation (ORIF) with volar locking plate provides stout fixation in volar Barton fractures and allows early physiotherapy and rehabilitation of wrist. The results are predictably good in most patients with minimal complications rates.